2021
DOI: 10.1186/s12889-021-12337-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of COVID-19 patients with prolonged incubation period and its implications for controlling the epidemics in China

Abstract: Background COVID-19 patients with long incubation period were reported in clinical practice and tracing of close contacts, but their epidemiological or clinical features remained vague. Methods We analyzed 11,425 COVID-19 cases reported between January–August, 2020 in China. The accelerated failure time model, Logistic and modified Poisson regression models were used to investigate the determinants of prolonged incubation period, as well as their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…For this reason, estimates of the tail percentiles were not robust to an incorrect parametric assumption of the incubation time distribution. In contrast to the pooled estimate of the 95th$$ {}^{th} $$ percentile based on earlier estimates (13.1 days 3 ), a recent study by Zhang et al 23 reported that more than 10% of individuals have an incubation time of more than 14 days. With our heavy‐tailed Burr distribution, assuming a gamma or Weibull distribution estimated the 99th$$ {}^{th} $$ percentile almost 4 days too small.…”
Section: Discussionmentioning
confidence: 72%
“…For this reason, estimates of the tail percentiles were not robust to an incorrect parametric assumption of the incubation time distribution. In contrast to the pooled estimate of the 95th$$ {}^{th} $$ percentile based on earlier estimates (13.1 days 3 ), a recent study by Zhang et al 23 reported that more than 10% of individuals have an incubation time of more than 14 days. With our heavy‐tailed Burr distribution, assuming a gamma or Weibull distribution estimated the 99th$$ {}^{th} $$ percentile almost 4 days too small.…”
Section: Discussionmentioning
confidence: 72%
“…In this investigation, we evaluated imported and locally exposed individuals separately since imported cases reported a longer delay from exposure to symptom onset. The discrepancy might be attributable to natural variability in exposure and immunity between travellers and locals, who are frequently younger ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the first place, isolation of the suspected cases with the minor disease at home is suggested. [13] Proper ventilation with good sunlight to destroy the virus is recommended at home. [14] Further, individuals suspected to have the disease should be asked to wear a surgical mask and to rehearse cough hygiene.…”
Section: Introductionmentioning
confidence: 99%